2004
DOI: 10.1111/j.1365-2303.2004.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of fine needle aspiration cytology of the breast: a comparison of cytological, frozen section, and final histological diagnoses

Abstract: This study examines the performance of the preliminary, on-site interpretation by the pathologist of fine needle aspiration (FNA) cytology smears compared to the final cytology report, the frozen section diagnosis and the final histopathological report. We found that both the preliminary and the final cytology reports gave satisfactory results over the minimum standards for quality assurance required by both the Norwegian breast screening programme and the NHS BSP in the UK with the exception of the 'suspiciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
3
2
Order By: Relevance
“…In addition, when the authors excluded the inconclusive cases, their level of agreement increased to 93.1 and 96.7%, respectively. The results were at variance with findings of Bofin et al [11], who reported 84.6% of correlation between cytological and histological diagnoses of mammary tumours.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In addition, when the authors excluded the inconclusive cases, their level of agreement increased to 93.1 and 96.7%, respectively. The results were at variance with findings of Bofin et al [11], who reported 84.6% of correlation between cytological and histological diagnoses of mammary tumours.…”
Section: Discussioncontrasting
confidence: 53%
“…Histologically, 25–30% of epithelial malignancies are in the group of specialized breast carcinoma like lobular, papillary, apocrine, tubular, cribriform, medullary, mixed, etc. [10,11]. In order to deciding the best type of treatment, sub typing of breast tumors using aspiration cytology is useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the practical setting, the C3 category is used when there is a level of diagnostic uncertainty. The number of C3 cases resulting in malignancy varies in the literature from 24.6 to 52% [19,20,21,22,23,24,25]. In this study, the overall rate of malignancy was 37.4%; however, the screening population yielded a much greater proportion of malignant outcomes at 50% when compared with the symptomatic population at 32%.…”
Section: Discussioncontrasting
confidence: 39%
“…There are enough evidence-based criteria to reliably categorise these lesions. A suspicious (C4) result usually suggests a high probability of cancer but is not as definitive as C5 either because of scant diagnostic material or low grade morphology (3,13,14). A non-diagnostic (C1) report provides limited information and highlights either sampling or technical problems.…”
Section: Leading Articlementioning
confidence: 99%